(untitled) (Harlow, England, 2018)
Understanding marketing management, capturing marketing insights, connecting with customers, building strong brands, shaping the market offerings, delivering value, communicating value, creating successful long-term growth.
Keywords: Tiếp thị,Marketing; Quản lý,Management; Châu Á,Asia